PEREIRA, Sofia L. B. y CRONEMBERGER, Izabel H. G. M. (2020) Serviço Social em tempos de pandemia: provocações ao debate. EDUFPI. Teresina. Pp. 472. - de Sá, Lundrigs; Emmendoerfer, Magnus Luiz (Espacio Abierto, 2022)
.